A study on perception toward email usage in the workplace at Majlis Bandaraya Bersejarah Melaka / Muhammad Ishkandar Ayub - Ayub, Muhammad Ishkandar (Faculty of Business and Management, 2013)
In this study, researcher wants to study the perception of employee in using the email at the workplace. In the modern world, technologies have become one of the important aspects in life, including doing job in the office. The theoretical framework applied the technology acceptance model(TAM) approach to examine the connection between perceive of usefulness and perceive ease of use with intention of using email at the workplace. Furthermore, the analysis was done using frequency analysis, descriptive statistics, reliability analysis and Pearson correlation coefficient for the purpose of testing the relationship between the variables. Survey data of 100 respondents from Majlis Bandaraya Melaka Bersejarah (MBMB) were tested with these models. The result from the study show that perceive of usefulness have more impact toward the email usage rather than perceive ease of use. This paper would offer compelling information pertaining to the factors which are highly potential in affecting MBMB employees to Use Email. Indeed, the outcomes of this study would be crucial for Employee of an organization in transferring information in the workplace.